Anti‐MDA5‐associated dermatomyositis. Issue 4 (8th April 2020) - Gupta, Rajiv; Kumar, Sunil; Gow, Peter; (Hsien‐Cheng) Chang, Leon; Yen, Linda
Abstract: Anti‐MDA5‐associated dermatomyositis (MDA5‐associated DM) is an uncommon presentation of idiopathic inflammatory myositis, typically amyopathic, associated with rapidly progressive, treatment refractory interstitial lung disease and poor prognosis, particularly in patients with concomitant rapidly progressive interstitial lung disease (RP‐ILD). We report two cases of MDA5‐associated DM with fatal outcome in one of the patients, despite 'aggressive triple therapy' for RP‐ILD.